LAJU SERANGAN PHOLADIDAE DAN TEREDINIDAE PADA BEBERAPA JENIS KAYU - Mohammad Muslich; Ginuk Sumarni; Nurwati Hadjib (Jurnal Penelitian Hasil Hutan, 1988)
The Mollusca  wood  borers,  normally  found  in Indonesian  sea waters, are divided  into  two  types,  i.e. Pholadidae  and Teredinidae.   Both  types  have different  characteristic  nature  of  infestation to  wood. This paper  deals with  a study on the borer  infestation   to  seven  tropical  commercial   wood  species.The  study   was  conducted at  Rambut Island  seashore  (on Java Sea)  using wood  samples  measuring  2.5 cm  by 5.0 cm by  80.0 cm.  The samples  were  randomly arranged at a raft  and  observed  after  8,  7 and  12 months.The  result  reveal  that  after 12  months most   of  the  samples  were  completely    attacked   by  the  Pholadidae  and Teredinidae.  However moderate  borer infestation was shown by  Eusideroxylon   zwageri, which  means that  this species  is relatively   resistant  to  marine  borers  infestation. Meanwhile,  the  infestation   rates  of  Pholadidae  and  Teredinidae   are significantly   different, and  they  have different characteristic